Main channels of party communication in Ukraine - Georgiievska, Viktoriia V.; Sydorenko Natalііa M.; Gerasymenko, Yevgen S.; Dubetska, Oksana O.; Yevdokymenko, Iryna M. (Linguistics and Culture Review, 2021)
The dynamics of the creation of the party press in Ukraine at the end of the 20th – beginning of the 21st century becomes obvious in the context of the emergence of new parties and the establishment of their journals. The main purpose of political communication is to inform, persuade, and mobilise the electorate. The quantitative indicators of the party press have changed because the number of parties has increased, as a result of which new publications have appeared more intensively. The party press is one of the most important sources of information about the party and its leader(s), the social orientation of the programme foundations; it is one of the main channels of communication with party members, supporters, and opponents. As a result of the development of information technologies, political parties started using internet resources to establish effective communication with more voters. The use of digital technologies, multimedia tools, bringing the information and propaganda activities of parties closer to the needs and opportunities of the readership in a certain way expands the social and communication horizons of party influence.